A cross-sectional study on eruption timing of primary teeth in children of Mysore, Karnataka - Mysore Devraj Indira; Nandlal Bhojraj; D Narayanappa (Wolters Kluwer Medknow Publications, 2018)
Context: Eruption of first primary teeth is the most anxiously awaited developmental milestone in a child. However, primary teeth have shown wide variations in their eruption time among different population, ethnic, and racial groups. Aims: The present study was conducted with the aim to evaluate the time and sequence of eruption of primary teeth of children of Mysore. Settings and Design: A cross-sectional study design included 1392 participants aged 3 months to 36 months recruited by simple random sampling method. The variables such as age, gender, and number of erupted primary teeth were recorded. Subjects and Methods: Clinical examination was done under natural illumination. A tooth was considered erupted when any part of its crown had penetrated the gingiva and was visible in the oral cavity. Statistical Analysis Used: Probit regression analysis was performed to obtain the mean and median age of eruption of teeth. The significance of difference in the mean age of eruption across gender and arch was determined using paired t-test. Results and Conclusion: The first primary tooth to erupt was mandibular central incisor at 10.24 ± 2.47 months followed by maxillary central incisor at 11.06 ± 2.65 months. The duration of primary teeth eruption was 17.89 and 18.32 months in males, 18.54 months and 18.32 months in females for maxilla and mandible, respectively. Eruption of primary tooth is delayed among children of Mysore as compared to standard eruption chart. The results will provide information to health professional about contemporary tooth eruption time derived from an Indian population.